Estudo de prevalência, gravidade e impacto da dor de dente na vida diária de crianças da cidade de Belo Horizonte - Eliane de Paula Reis Barretto (2003)
The relationship among buccal health, well-being and life quality has been receiving larger attention of the Dentistry, with views his/her approach of the proposal of promotion of health. In this context, considerations on the toothache, source motivator of expressive part of the dental consultations, become relevant. Like this, the objectives of this study went to evaluate the prevalence, the gravity and the impacts of the toothache in the children's of the city of Belo Horizonte daily life. They participated in the research 601 students of the nets municipal, state andpeculiar of teaching, eight nine years old and their responsible. The distribution of the sample for regional and teaching nets based on the number of schools distributed in the municipal district. Through random draw, nine schools were visited. The collection of data was accomplished by the application of a questionnaire to the parents, and of interview, clinical exams and a scale of faces to the children, instruments previously tested in two study-pilot. The research was approved by the Ethics Committee in Research of UFMG and terms of free andillustrious consent were signed by each one of the responsible and participant schools. The devolution tax was of 88,1%. The data were processed in the program Statistical Package is Social Science and applied the tests qui-square and odds ratio. The results revealed that: children in the eight nine year-old age group, in Belo Horizonte, have a high toothache prevalence (45,9%); the more high the degree of maternal education and the economical group to which the child belongs,smaller the prevalence and the gravity of the toothache; the children, in this age group, suffer plenty impacts in their life quality, in function of the damage to their daily activities and of the risks to the general health imputed by the toothache; parents and responsible they also suffer great damages in their normal activities because of the infantile toothache; the impacts for the child's life were similar among the three researched economical groups and among the mothers' children with different education degrees; the gender didn't have influence in the experienceof infantile toothache, either in the gravity or impacts; the toothache experience in 201 the children was associated to you cause pathological, mainly to dental and periodontal problems, in other words, to the worst buccal clinical condition; children with these alterations presented, respectively, 1,90 and 1,92 times more chance of having toothache of what those without such alterations; already for the gravity andthe impacts of the toothache pathological and physiologic factors competed equally, without predominance of some on the other ones. However, the pathological factors infer larger pain intensity.